Santuário de Caravaggio e a modernização de espaços sacralizados: notas etnográficas de uma romaria na serra gaúcha = Caravaggio sanctuary and the modernization of sacred spaces : ethnographic notes of a pilgrimage in the Serra Gaúcha - Lopes, José Rogério (Ciencias sociales y religión, 2012)
This article discusses some modernizing elements present in the rites of pilgrimage and devotion of popular religiosity, in Brazilian Catholicism, more specifically, in the Pilgrimage of N. Mrs. Caravaggio in Farroupilha city, RS. The problematic proposal considers the structure and spatiality of the Sanctuay in the city, the path of pilgrimage for devotees in central days of this festival and the discourses and logics of appropriation of symbolic goods in devotion. The operating logic of the actors-devotees interwoven in this “act of faith”, typical of Marian devotions, establish themselves in practices that weave gestures themselves, weft comprehensive meanings important to the composition, rupture or update of popular religiosity, which in more recent times, are “faced” by modernizing rationality that (re)configures the space/time devotee of the act. Followed this context, power will also see, interspersed with ritual structure of the Pilgrimage of Caravaggio, a regional identity that remains now latent, sometimes manifested in devotional rituals that event.